Investigating the Arabic /f/ Pronunciation: A Comparative Analysis of Acoustic Phonetics - Mad Ali; Anwar Sanusi; Hikmah Maulani; Nalahuddin Saleh; Shofa Musthofa Khalid; Rinaldi Supriadi; Mohamad Zaka Al Farisi (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2023)
This study aims to understand the mispronunciation of the consonant /f/ in Arabic by Javanese Speakers (JS), Sundanese Speakers (SS) and Batak Speakers (BS). The focus is on the sound /f/ as it can shift to /p/ when spoken by speakers of various L1 languages. Javanese, Sundanese, and Batak were chosen because of their prominence in Indonesia. Using a descriptive-evaluative-comparative approach, the researchers analyzed the pronunciation of /f/ by JS, SS, BS, contrasted with a native speaker (NS), Sheikh Misyari bin Rasyid Al-'Afasi. The research data was in the form of sound recordings of the recitation of nine verses of the Quran with the sound /f/, collected using the listen-record-pay-attention technique and analyzed acoustically through Praat. The findings reveal phonetic interference in pronouncing/f/ at the beginning, middle, and end of words by SS and BS. In JS, it only occurs at the beginning and the end. The absence of sound /f/ in the phonological system of local languages can cause this interference. The implication lies in learning to listen and speak Arabic, helping to design strategies to overcome pronunciation errors when encountering foreign sounds in the learner's phonological system.